GENDER DIFFERENCES IN THE LENGTH OF WRITING - I Putu Yogi Pratama; Kadek Erlita Dwiyanti; Ni Putu Ines Marylena Candra Manik (Universitas Pendidikan Ganesha, 2020)
It is generally accepted that gender relates to language. This study aimed to investigate the relationship between gender and language by finding out the differences in the length of writing between male and female students as well as the factors affecting the length differences. Moreover, this study was designed as a descriptive quantitative study. There were 30 students consisting of 15 male students and 15 female students as the participants wrote a recount text about their bad experiences. The findings showed that there was a significant difference between female and male participants in the number of wording of writing. The female students had a longer size of writing than male students as indicated from the complexity of the sentences. Apart from that, the difference was also due to the development of the writing which includes the description of their feelings and the use of five features namely intensifying, hedging, tag questions, empty adjectives, and adverbs.